Temporal trends in mortality from hepatic neoplasia in adults in the southern states of Brazil from 2000 to 2019 (Research, Society and Development, 2023)
Goals: To analyze temporal trends in mortality from liver cancer in adults in the southern states of Brazil from 2000 to 2019. Method: An ecological time series study was conducted. All records regarding mortality from liver cancer in the southern states of Brazil in the period between 2000 and 2019 were analyzed. Mortality rates were calculated and standardized by sex, age by sex and state. Simple linear regression was performed to estimate the trend of mortality. The result obtained is statistically significant (p